Effects of product display and gender on consumer purchase behaviour. - Chen, Yanling. (2008)
The purpose of this study is to examine the effects of gender on retail consumers, and the coordination and juxtaposition of the outfit on consumer purchase behaviour. Results indicated that purchase behaviour is affected by the above three factors (gender, coordination, juxtaposition).